PREPARATION AND IN VITRO EVALUATION OF CANDESARTAN CILEXETIL–BASED NANOPARTICLES AS FAST DISSOLVING ORAL FILM - ABDULRAZZAQ, INAS F.; OUDAH, MALATH H.; AL-SHAIBANI, ABULFADHEL; SALAL, YASMIEN A. (International Journal of Applied Pharmaceutics, 2026)
Objective: The present work aims to formulate candesartan cilexetil (CC) as nanoparticles oral film to enhance solubility of CC, and promote its dissolution rate, and this could produce rapid therapeutic action of drug. Methods: The nanoparticles prepared by solvent/antisolvent precipitated method then formulated as fast dissolving oral films by casting method.CC nanoparticles formulated by different polymer: drug ratio which was 1:1 and 2:1 hydroxypropyl methylcellulose (HPMC), and polyvinylpyrrolidone (PVP) with different molecular weight like, HPMCE5, HPMCE50, PVPK15 and PVPK30. The effect of polymer type, polymer ratio and injected volume on the size and specific surface area of prepared particle were tested. Results: The bested formula FCC3 was found with a smallest size equal to 37 nm and specific surface area of 54.66m2/g. The FCC3 formula was dried by freeze drier and tested by field emission scanning electron microscope (FESEM), differential scanning calorimetry (DSC) and X-ray powder diffraction analysis (XRD) to determine surface morphology, crystallinity and compatibility, then formulated as fast dissolving oral film. The drug content in the 4 cm2 prepared film was distributed between 93.00% ± 1.75 to 98.25% ± 1.25 and disintegrate in 25min. The in vitro release of candesartan nanoparticle from oral film was 68% in 2 minute and complete to 100% at 4 minutes. Conclusion: The results confirmed fast release and better dissolution rate of prepared candesartan nanoparticle than pure drug.